Comparative evaluation of the cyclic fatigue resistance of R-Motion® in comparison to two competitive systems: An in vitro study based on a case report - Jordy , K.; Malvicini, G.; Tavakkoli, A.; Gaeta , C.; Grandini, S. (Journal of Osseointegration, 2024)
Aim To compare the cyclic fatigue resistance of R-Motion® with two competitive file systems (WaveOne Gold® and Reciproc Blue®) in a simulated root canal based on a case report. Methodology A metal replica, designed as a copy of the length and curvature of a mesiobuccal canal of an upper first molar originating from a case report, was used as a test phantom to measure the cyclic fatigue resistance of the following files: R-Motion® 25, WaveOne Gold® primary, and Reciproc Blue® R25. A total of 16 file per group were tested in the same reciprocation motion and cyclic fatigue was measured as time to file fracture. An unpaired t-test was used to analyze the data. Results A statistically significant difference (P < 0,05) was noted between R-Motion® 25 files and WaveOne Gold® primary files. A statistically significant difference (P < 0,05) was noted between R-Motion® 25 files and the Reciproc Blue® R25 files. R-Motion® 25 files were associated with a significant increase in the meantime to fracture when compared to WaveOne Gold® primary files (397,69 ± 66,63 vs 173,50 ± 24,60, respectively) and the Reciproc Blue® R25 files (397,69 ± 66.63 vs 205,13 ± 39.43, respectively). Conclusion R-Motion® 25 file showed a significantly higher cyclic fatigue resistance compared to WaveOne Gold® primary file and the Reciproc Blue® R25 file.